O LUGAR DA LITERATURA MONÁSTICA FEMININA NO CÂNONE BARROCO PORTUGUÊS - PETRESCU, Cristina (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Women’s Monastic Writing within the Portuguese Baroque Canon. This article aims to approach Portuguese female monastic literature of the seventeenth and eighteenth centuries in terms of its relationship with the Baroque literary canon. Shaped at the border that separates voice and silence, the visible and the spiritual universe, the cult of moderation and the desire to assert, this literature outlined a new type of discourse, which hinted at the intense conflict between suppression and authority, which, in turn, gave rise to a permanent dialogue between the feminine ethos, the controversial character of the Baroque and the always oscillating essence of the canon. We will show, that, during the last centuries, the works of some famous female writers, such as Sóror Maria do Céu, Sóror Violante do Céu and Sóror Madalena da Glória, or of other female authors who remained in the shadows, have been differently and unequally absorbed by literary critics and historians and by great anthologists. Their writings have not ceased to be represented as preferential places of dispute, of the uninterrupted dialogue between silence and affirmation, between center and margin, which generally regulates the literary canon. REZUMAT. Literatura monastică feminină în cadrul canonului baroc portughez. Acest articol își propune să abordeze literatură monastică feminină portugheză a secolelor XVII-XVIII prin prisma relației cu canonul literar baroc. Plăsmuită la granița dintre glas și tăcere, dintre universul vizibil și cel spiritual, dintre cultul moderației și dorința de afirmare, această literatură a conturat un nou tip de discurs, ce a lăsat să se întrevadă intensul conflict dintre suprimare și autoritate care, la rândul său, a dat naștere unui permanent dialog între ethosul feminin, caracterul controversat al barocului și esența mereu oscilantă a canonului. Vom arăta că, pe parcursul ultimelor secole, operele unor scriitoare de renume, ca Sóror Maria do Céu, Sóror Violante do Céu și Sóror Madalena da Glória, sau ale unor autoare ce au rămas în umbră, au fost absorbite în mod diferit și inegal de criticii și istoricii literari și de marii antologiști. Scrierile lor nu au încetat și vor continua, cel mai probabil, să fie reprezentate ca locuri preferențiale ale disputei, ale neîntreruptului dialog dintre tăcere și afirmare, dintre centru și margine, ce reglementează, în genere, canonul literar. Cuvinte-cheie: monastic, literatură, feminin, canon, baroc